2019
DOI: 10.1589/jpts.31.802
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of simulation method to improve efficiency of chair-to-wheelchair transfer of patients performed by caregivers

Abstract: [Purpose] We aimed to clarify whether demonstration and simulated experience help the ability of care-receivers to get transferred, such as from the bed to the commode. [Participants and Methods] Participants included 28 nurses and 17 caregivers (34 females and 11 males). We developed a total floor reaction force measurement device to quantify the total loading level of care-receivers and caregivers and force shoes to quantify the loading level of the caregivers. Using these instruments, we constructed a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We have already reported that simulated experience method is an effective method to promote utilization of care recipient power who had a limited range of motion in hip joint by caregiver 5 ) . Results of this research suggest that hemiplegia and limited-ROM-in-multiple-joints are added as dysfunctions that can be applied to the simulated experience method in transfer assistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already reported that simulated experience method is an effective method to promote utilization of care recipient power who had a limited range of motion in hip joint by caregiver 5 ) . Results of this research suggest that hemiplegia and limited-ROM-in-multiple-joints are added as dysfunctions that can be applied to the simulated experience method in transfer assistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the load on the lower limbs of the care recipient at the time of the buttocks leaving the seat used as the index of transfer ability 12 ) . A measurement system consisting of two measurement devices, to quantify total floor reaction force and hip-floor reaction force, and force shoes, was used 5 ) . Each device is made of a stainless steel panel and load cells (LMB-A-2KN-P; Kyowa Electronic Instruments Co., Ltd., Tokyo, Japan).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In supporting standing-up, the required force is considered to be the difference between the patient's weight and ground reaction force exerted by the patient. Nakano et al (2019) suggested that wearable force shoes could measure the required forces while supporting standing-up (Nakano et al, 2019). Regarding lumbar loads, stress of the vertebral (L4-L5) joint and activities of spinae erector muscle are considered as important factors.…”
Section: Introductionmentioning
confidence: 99%